An index to characterize the multi-dimensional nature of land use regulations in the Greater Houston Metropolitan Area - Luis Estevez (REGION, 2018)
Although housing prices and the lack of real income growth are cited as the main factors behind the housing affordability problem, it has been proven that land use regulations have some responsibility as well. Indices have been the most common indicator used to characterize the stringency of local land use regulations; however, these studies focus primarily on those most stringent regulatory environments, and therefore there is no evidence of the validity of such indices in areas regarded as less stringent. In response to this lack of evidence, using a unique data set this article presents an index characterizing local regulatory environments in a well-known less stringent regulatory environment: the Houston-Galveston Area in Texas. This index proves to be a valid measure capable of capturing the multi-dimensional nature of land use regulations. The analysis of the index and statistical correlations validate the use of indices to characterize metropolitan land use regulations.
Keywords: 330; Land use regulations; affordable housing; index